Features of the language implementation of the concept of «culture» in social networks - Zhumanbekova Н.З.; Ryspayeva Д.С. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
This article is devoted to the problem of cognitive-pragmatic features of Twitter and Instagram blogs as web communication texts. Web communications are various texts on social networks in the global Internet space, contributing to the emergence of a new sociocultural environment and linguistic reality. Recently, they have become the subject of linguistic research. Web communication studies address such issues as the structural characteristics of the Internet language, morphological and syntactic features, paragraphic tools; genre characterization of text types in Internet communication; language features of chatting, language changes caused by the Internet. In describing the cognitive-pragmatic features of the modern English language of web communications, a combined approach of principles and research methods was used. The theoretical part presents a review of the literature on the theory of web communications, cognitive linguistics and pragmalinguistics, the practical part contains an analysis of the texts Twitter and Instagram to identify cognitive-pragmatic features of the English language